Diglossia and Language Attrition Among Col Language Speakers in Lubuklingga as EFL Speakers - Seli, Sastika; Syafitri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims at 1) identifying the variety choice among native Lubuklinggau as EFL speakers between H and L variety and 2) explaining the attrition as the effect of language attitude. This is a descriptive-qualitative research. The data were collected from questionnaire and interview derived from 17 participants who are the Col language speakers in Lubuklinggau as EFL speakers. The result shows that H variety is preferred to use in public speaking, talking to a superior and doing assignment. L variety is used in chatting online, and talking to someone close. By analyzing the data, it is also found out that the informants has positive attitude toward their H and L variety to use them in different settings. Therefore, the language attrition can be fainted to avoid the language shift or lost. Keywords: Col Language, Diglossia, Language Attitude